PENGARUH APLIKASI E-LAPOR TERHADAP KINERJA APARATUR SIPIL NEGARA KOTA BIMA (Studi Kasusu Dinas Pekerjaan Umum Dan Penataan Ruang Kota Bima) - Sukardin, Sukardin; Dharmayanda, Hardian Reza; Hidayati, Sri Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
AbstractThere are still many people who have difficulty following regulations or policies in obtaining services so that the services obtained become longer, besides that the State Civil Apparatus that provides services is less responsive because their competence is not up to standard, there are still inefficiencies or lack of evaluation of their work programs causing the performance carried out less optimally because it hinders the improvement of performance quality bureaucrats The purpose of this study is to determine the influence of the E-Report Application on the performance of the Bima City State Civil Apparatus, especially employees in the Bima City Public Works and Spatial Planning Office and How the effectiveness of the E-Report Application on the performance of the Bima City State Civil Apparatus, especially in the Bima City Public Works and Spatial Planning Office. The research method used in this study is a quantitative research method. The data collection technique used in this research was based on questionnaires (questionnaires) and documentation, for the samples used in this study used sampling techniques with a total of 49 respondents of the Bima City State Civil Apparatus, especially employees at the Bima City Public Works and Spatial Planning Office. The data analysis technique used in this study is path analysis with the help of a program using statistical software Jamovi 2.3.16. The results of the study can be stated that the existence of the E-report Application has a significant influence on the performance of employees, especially the State Civil Service in the Public Works and Spatial Planning Office of Bima City, the existence of the E-report Application is able to intervene in changes in employee performance in the Dinas even though it is only 13%.